2014
DOI: 10.1111/1753-0407.12128
|View full text |Cite
|
Sign up to set email alerts
|

Variations in CCR5, but not HFE, ELMO1, or SLC12A3, are associated with susceptibility to kidney disease in north Indian individuals with type 2 diabetes CCR5变异而不是HFEELMO1或者SLC12A3变异与印度北部的2型糖尿病患者的肾病易感性相关

Abstract: This study shows that the CCR5 AA genotype is over-represented in subjects with kidney disease due to type 2 diabetes. The CCR5 59029G>A and ELMO1 (+9170 G>A) loci are more frequent, and the SLC12A3 34372 AA genotype is associated with a reduced risk of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 45 publications
(98 reference statements)
4
33
0
1
Order By: Relevance
“…The significant association of the ELMO1 (engulfment and cell motility 1) rs741301 (Int18+9170 A/G) variant with type 2 diabetic nephropathy found in the present study is similar to that reported in Japanese (Shimazaki et al., ) and Chinese population (Wu et al., ) and in contradiction to that reported in Mexican Americans (Kim et al., ) and north Indians (Yadav et al., ). Though the association of rs741301 SNP with DN was not replicated in American Indian(Hanson et al., ) and African American population (Leak et al., ), other SNPs in intron 13 of the ELMO1 gene were found to be associated with nephropathy in those studies confirming the candidature of ELMO1 gene in the susceptibility to nephropathy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The significant association of the ELMO1 (engulfment and cell motility 1) rs741301 (Int18+9170 A/G) variant with type 2 diabetic nephropathy found in the present study is similar to that reported in Japanese (Shimazaki et al., ) and Chinese population (Wu et al., ) and in contradiction to that reported in Mexican Americans (Kim et al., ) and north Indians (Yadav et al., ). Though the association of rs741301 SNP with DN was not replicated in American Indian(Hanson et al., ) and African American population (Leak et al., ), other SNPs in intron 13 of the ELMO1 gene were found to be associated with nephropathy in those studies confirming the candidature of ELMO1 gene in the susceptibility to nephropathy.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that the rs11643718 SNP (Arg913Gln) in exon 23 of SLC12A3 gene showed a dramatic change in the protein structure when the Arg913 wild‐type allele was substituted by the Gln mutant allele when analysed using bioinformatics tools such as Transcription Element Search System and Protein Structure Prediction Server (Abu Seman et al., ). The minor allele (“A”) of this SNP accounted for reduced risk for type 2 diabetes and/or nephropathy in Japanese (Tanaka et al., ), Malaysian(Abu Seman et al., ), north Indian (Yadav et al., ) and south Indian population (present study), whereas it was not associated with nephropathy in American Caucasians(Ng et al., ). Hence, the effect of this SNP in type 2 diabetes and nephropathy is perhaps specific to Asian populations.…”
Section: Discussionmentioning
confidence: 52%
“…Variations in CCR5 are associated with susceptibility to kidney disease in patients with type 2 diabetes. CCR5 AA genotype is over-represented in subjects with kidney disease due to type 2 diabetes [26]. Research has also shown that blockade of CCR5 improved renal function after ischemia-reperfusion injury of the kidney [27].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed the association of different SNP variants in the ELMO1 gene with susceptibility to DKD in patients from various populations: African Americans [20], European Americans [21], American Indians [22], Mexican Americans [23], Tunisian Arabs [24], as well as citizens of China [25], India [26][27], Iran [28], and Malaysia [29]. Unfortunately, it is impossible to draw a unified conclusion from the outcomes because these studies were different in terms of methodology and definition of DKD.…”
Section: Snp Genotypingmentioning
confidence: 95%
“…Unfortunately, it is impossible to draw a unified conclusion from the outcomes because these studies were different in terms of methodology and definition of DKD. Some of these patients presented with T2DM [20,[22][23][24][25][26][27][28][29], but others with type 1 diabetes mellitus [21]. Some of the authors used the DKD definition according to ADA [3,28] whereas others according to NKF [12,21,25,26,30].…”
Section: Snp Genotypingmentioning
confidence: 99%